«Purpurowy płomień»: Helena Grossówna w Operze Pomorskiej i Teatrze Toruńskim - Artur Duda (Pamiętnik Teatralny, 2017)
The article presents little known biographical facts about Helena Grossówna, one of the stars of the Polish film industry in the 1930s. Born in Toruń, the artist started out her career as a member of a ballet company for fledging dancers founded at the Toruń theatre during the first directorship of Karol Benda (1924-1926), which culminated in the opening of the Pomorska Opera. At the time, Grossówna was able to improve her dancing skills by performing in operas, operettas, and musical comedies. Having travelled to France, where she took classes from Matylda Krzesińska and Bronislava Nijinska (Vaslav Nijinsky’s sister), Grossówna returned to Toruń and worked as a choreographer at the Toruński Theatre, run again by Karol Benda (1930-1932). The article contains as detailed a description as the scant source materials permit of Helena Grossówna’s performance as Salome in Golgota [Golgotha] by Bolesław Rosłan (dir. Józef Cornobis, 1931), and it presents strong evidence that Grossówna left Toruń as a fully fledged artist.